ASSESSING LIVEMOCHA AND DUOLINGO EVALUATION TASKS: ADAPTING CHAPELLE CALL ASSESSMENT CRITERIA IN AUTONOMOUS LEANING EXPERIENCE - I Irham (Erudio Journal of Educational Innovation, 2018)
Computer assisted language learning has been the major issue in the recent decades. Several free networking sites focusing on language learning are offered abundantly. Nonetheless, most of the extant studies seem to compare the traditional way of learning language and modern one per se. This paper, on the other hand, will focus on task evaluation of CALL system as proposed by Chapelle (2001). Six criteria of CALL assessments; language learning potential, learner fit, authenticity, meaning focus, positive impact, and practicality, will be employed to delve Livemocha and Duolingo’s language learning task on Dutch course for basic level. The researcher here plays role as the key instrument in which the data were gained through the experience of using Livemocha and Duolinggo. The Dutch, as foreign language, is chosen as the subject to be studied. As the results, it is intriguing that Livemocha’ task for Dutch course is not adequately fit to beginner leaners. Meanwhile, its counterpart questionably complies authenticity point. The beginner learners may efficiently make use of computer assisted language learning tool to foster their study on foreign language. Nonetheless, they have to be aware of which tool can accelerate their purpose better.